A catalogue of energy conservation measures (ECM) and a tool for their application in energy simulation models. (May 2020) - Costa, Gonçal; Sicilia, Álvaro; Oregi, Xabat; Pedrero, Juan; Mabe, Lara
Abstract: One of the primary objectives in the refurbishment of buildings is to identify the best combination of Energy Conservation Measures (ECMs) in terms of energy efficiency. The current Building Energy Performance (BEP) simulation tools require a great deal of time and effort because data from multiple sources must be properly combined (e.g., building/urban models, ECM catalogues, weather condition files) in order to create energy simulation models. In addition, the process of manually setting up each scenario in order to obtain the most optimal solution is also a demanding and time-consuming task. The growing presence of the Building Information Model/Modelling (BIM) technologies in the Architecture, Engineering and Construction (AEC) industry, combined with the new capabilities to link and integrate data using Semantic Web technologies, is presented as an alternative to automate the simulation process. In this article, we present a system that takes advantage of the capabilities of these technologies to integrate ECM data into BEP simulation models in an automated way. The system is composed of a catalogue of ECM measures described in Resource Description Framework (RDF) and a software component that facilitates their application in the models. The system has been developed in the context of OptEEmAL, a research project aimed at creating a web platform to facilitate building simulations at a district scale. The applicability of the system is demonstrated in a case study of a district-scale project.